Comparing autism, pdd-nos, and other developmental disabilities on parent-reported behavior problems: little evidence for asd subtype validity. - Snow, Anne; Lecavalier, Luc (Journal of Autism & Developmental Disorders, 2011)
Studies on the distinction between Autistic Disorder (AD) and Pervasive Developmental Disorder Not Otherwise Specified (PDD-NOS) have been inconclusive. This study examined the validity of PDD-NOS by comparing it to AD and other developmental disorders (DD) on parent-reported behavior problems. Fifty-four children with PDD-NOS were individually matched on age and non-verbal IQ to 54 children with AD and 54 children with DD. Groups were compared on select subscales of the Child Behavior Checklist. High rates of psychopathology were observed in both ASD groups. The only difference between PDD-NOS and AD groups was higher scores in the PDD-NOS group on two items measuring Anxiety/Depression. Cognitive functioning may be a more salient variable than subtype when studying psychopathology in individuals with ASDs.